Analisis Yuridis Dasar Hukum Pengembalian Berkas Perkara oleh Jaksa (Penuntut Umum) kepada Penyidik - Mohd. Yusuf Daeng M.; Desye Shonarista Lumban Gaol; Mutia Ayu Lestari; Jihan Faiza Ramadhani; Geofani Milthree Saragih (Departement of Mathematics Education, 2023)
The pre-prosecution process often occurs, so that the case files go back and forth from investigators to the Public Prosecutor, incomplete case files will have an impact on the pre-prosecution process. The purpose of this study is to determine the return of case files by the Public Prosecutor in pre-prosecution. This type of research is normative legal research with a case approach, legislation, and analysis. The results of the study were obtained as follows, because there is no single provision that provides a limit on the number of times case files can be returned, this can be related to the legal objectives of a person's human rights, and for the sake of legal certainty for justice seekers, the return of investigation results or additional investigator results by The Public Prosecutor to investigators, must have strict limitation criteria. The consequences if the case file is not returned from the public prosecutor if within seven days the case file is not returned, the investigation case file is considered complete.